Advanced Content Networking: A Literature Review of Information-Centric Networking, Edge Computing, and Intelligent Content Delivery (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The explosive growth in multimedia data flow, cloud-based services, mobile apps, and IoT devices is changing the needs of today's network infrastructures. The classical Internet designs based on hosts are facing difficulties with meeting the need for reduced latency, improved scalability, effective content delivery, and overall user experience. Thus, advanced content networking has become an essential research field associated with content delivery in the context of content-centric architecture, edge computing, intelligent caching, and software defined networks. This literature review analyzes scientific progress in advanced content networking between 2016 and 2026, paying attention to Information-Centric Networking, Content-Centric Networking, Named Data Networking, edge computing, cloud-to-edge continuum architectures, and artificial intelligence content delivery. Comparative findings from the reviewed literature indicate that Information-Centric Networking architectures, particularly Named Data Networking, improve network performance through in-network caching and content-based routing. Studies report cache hit ratio improvements of approximately 20–40%, reductions in backbone traffic, and lower end-to-end latency compared with conventional host-centric architectures. However, these benefits are offset by challenges related to forwarding-table scalability, name-based routing complexity, and cache management, highlighting the performance trade-offs that remain barriers to Internet-scale deployment.